Synthesis and Characterisation of Novel Cobalt(li),Copper (II) and Mercury (II) Complexes of Poly Vinyl Urethanised Oxime. - AI-Jeboori, M.J.; Numan, A.T.; Ahmed `, D. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The reaction  of poly (vinyl  alcohol) (PV A) with Urea in (DMSO)resulted  in uerthanised oxim, wr,ich reacted with diacetylmonoxime  in a (DY.ISOfmethanol) to give anew type (N2) polymeric bidentate imine oxime ligand [HL], The ligand was reacted with MCh (where M= Co, Cu, and Hg). Under  reflux in a (DMF/Methanol) mixture with (I:1) ratio to give Complexes  of the general formula [M (T.)2]X, (where M=Co,Hg,  Cu). All .:ompouncs have been characterized  by spectroscopicmethods  [IR,  U.V.-Vis, A tomi